The genus Planaeschna McLachlan, 1895 and its subgroupings in Vietnam, with descriptions of three new species (Odonata: Aeshnidae) - Kompier, Tom; Karube, Haruki; Futahashi, Ryo; Phan, Quoc Toan (Zootaxa, 2021)
Twelve Planaeschna McLachlan, 1895 species recorded in Vietnam are presented and their subgroupings based on nuclear DNA analysis are discussed. Three new species are described (Planaeschna crux sp. nov. [holotype: Pia Oac NP, Cao Bang Prov.], Planaeschna samurai sp. nov. [holotype: Khau Pha, Tu Le, Yen Bai Prov.] and Planaeschna tsuchi sp. nov. [holotype: Xuan Son NP, Phu Tho Prov.]. Planaeschna celia Wilson & Reels, 2001 is recorded from Vietnam for the first time. Planaeschna guentherpetersi Sasamoto, Do & Vu, 2013 is shown to be a subspecies of Planaeschna ishigakiana Asahina, 1951. The female of Planaeschna cucphuongensis Karube, 1999 is described for the first time. Additional records are provided for Planaeschna asahinai Karube, 2011, Planaeschna tamdaoensis Asahina, 1996, Planaeschna tomokunii Asahina, 1996, and Planaeschna viridis Karube, 2004. Lastly, the females of two unidentified Planaeschna spp. are illustrated. Information on the ecology of all species is provided.